Coronary artery events in Thai patients with psoriasis using Framingham and Ramathibodi Electricity Generating Authority of Thailand risk scores - Sakunee Khankham (2018)
Background: Psoriasis is an independent risk factor for cardiovascular disease. Several tools such as Framingham score (FRS) and Ramathibodi-Electricity Generating Authority of Thailand (RAMA-EGAT) score have been developed to predict the 10-year risk of coronary artery disease (CAD) and death. However, there are only few studies determine CAD risk using FRS and RAMA-EGAT score in Asian patients with psoriasis. Objectives: To investigate the risk of CAD events using the FRS and RAMA-EGAT score in Thai patients with psoriasis. Methods: Predictive factors that associated with intermediate and high risk (≥10%) of CAD events within 10-year were determined. Variables, including age, sex, blood pressure, cholesterol, high-density lipoprotein, diabetes mellitus, waist circumference, smoking, and alcohol intake were used to calculate scores. Results: Of 145 patients with psoriasis and a mean age of 48.1 ± 14.1 years, 72 patients were men. Using FRS and RAMA-EGAT, 25% and 13% of the patients, respectively had a ≥10% risk of developing CAD events. A higher risk of CAD was predicted when severe psoriasis was considered. The duration of disease and treatment were associated with an increased risk of CAD using the FRS and RAMA-EGAT score by multivariate analysis. Conclusions: A substantial portion of our patients had a CAD risk ≥10%, with significant relationship with duration of disease and treatment. Early screening of CAD and appropriate treatments of psoriasis may be helpful for preventing CAD in patients with psoriasis.